The doctrine of loss of chance: a saviour in cases of unclear causation? - Jahn Kassim, Puteri Nemie (LexisNexis Malaysia Sdn Bhd, 2003)
In proving negligence, one of the elements which the plaintiff must prove is that the damage suffered was caused by the defendant's negligence. In other words, the burden of proof lies on the plaintiff to prove causation. The standard of proof requires the plaintiff to show on balance of probabilities that, in the absence of the breach, he would not have suffered the injury. 1 Proof on the balance of probabilities means that if something can be proved fifty-one percent likely, then it is treated as having occurred, and, if proved forty-nine percent likely, it is held not to have occurred. 2 In medical malpractice context, the patient must demonstrate that there was a reasonable medical probability that the doctor's negligence caused the patient's injuries. The phrase reasonable medical probability means more than fifty percent chance that the negligence caused the injury. 3 If the plaintiff fails to prove causation on balance of probabilities, then the plaintiff gets nothing in term of damages. 4